Dampak Literasi Keuangan, Literasi Ekonomi, dan Pendapatan Terhadap Pengelolaan Keuangan Pribadi Generasi Z (Studi Kasus Pada Mahasiswa FEB UTS) - Suwardi, Didi; Cita, Fitria Permata; Oktapiani, Serli (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the effect of financial literacy, economic literacy, and digital awareness of the millennial generation on personal financial management, with a case study on students of the Faculty of Economics and Business, Sumbawa University of Technology (FEB UTS). This research uses a quantitative approach and analyzes data through the SEM-PLS (Structural Equation Modeling-Partial Least Squares) method. The independent variables in this study include financial literacy, economic literacy, and digital awareness, while the dependent variable is personal financial management. The population in this study consists of FEB UTS students who fall into the Generation Z category, with an unknown number; to determine the population, the Paul Leedy formula was used. The research sample was selected using total sampling technique or saturated sampling. Data was collected through a questionnaire using a 1-4 Likert scale, which was distributed to 100 respondents of FEB UTS students who belong to Generation Z. The results of the analysis show that financial literacy, economic literacy, and digital awareness have a significant influence on personal financial management. This research is expected to contribute to the development of more effective financial education programs among students, and can be used as a basis for educational institutions and the government in designing financial literacy policies that suit the needs of Generation Z.